Itch in Children with Type 1 Diabetes: A Cross-Sectional Study - Aleksandra A. Stefaniak; Agnieszka Zubkiewicz-Kucharska; Łukasz Matusiak; Anna Noczyńska; Jacek C. Szepietowski (Adis, Springer Healthcare, 2020)
Abstract Introduction Type 1 diabetes (T1D) is reported to be one of the most common medical conditions in school-age youth and is ranked third in the prevalence of pediatric conditions. Only a few studies have investigated the occurrence of itch in diabetes mellitus, reporting conflicting data. The purpose of this study was to investigate the prevalence of itch in T1D to provide itch characteristics and to explore the potential underlying causes. Methods This prospective study evaluated itch among 100 children with T1D. Itch intensity was assessed with the Numerical Rating Scale (NRS) and the 4-Item Itch Questionnaire (4IIQ). The Children's Dermatology Life Quality Index (CDLQI) was implemented to assess the quality of life issues. Various clinical features and factors influencing itch were also examined. Skin dryness was evaluated clinically by non-invasive assessment of epidermis moisturizing. Results Itch occurred in 22% of children with T1D with the mean maximal intensity of 5.9 ± 3.0 points in NRS and 6.7 ± 3.5 points in 4IIQ (median, 5.5 points). In the majority of patients, the itch was limited to a few regions of the body; usually, the upper limbs (68.2%) were affected, followed by the lower limbs (50%) and the trunk (31.8%). Clinically examined skin xerosis was significantly more advanced in children with itch compared with those without itch (p < 0.01). The mean CDLQI score in the itchy group was 4.0 ± 4.7 points (median, 2.5 points), indicating a small impairment of quality of life. The intensity of itch (both NRS last 3 days and NRS last 24 h) correlated positively with life quality impairment (R = 0.7; p = 0.015 and R = 0.8, p = 0.002, respectively). Conclusions Our study found itch as a moderately frequent symptom in children with T1D; however, itch presence and intensity may relevantly debilitate quality of life among subjects. We suggest that dryness of the skin may play a role in the pathogenesis of itch in this population.